THE IMMUNOPROTEASOME, THE 20S PROTEASOME, AND THE PA28αβ PROTEASOME REGULATOR ARE OXIDATIVE-STRESS-ADAPTIVE PROTEOLYTIC COMPLEXES - Pickering, Andrew M. (2010)
Oxidized cytoplasmic and nuclear proteins are normally degraded by proteasome, but accumulate with age and disease. We demonstrate the importance of various forms of the proteasome during transient (reversible) adaptation (hormesis), to oxidative stress in murine embryonic fibroblasts. Adaptation was achieved by ‘pre-treatment’ with very low concentrations of H(2)O(2), and tested by measuring inducible resistance to a subsequent, much higher ‘challenge’ dose of H(2)O(2). Following an initial direct physical activation of pre-existing proteasomes, 20S proteasome, immunoproteasome, and PA28αβ regulator, all exhibited substantially increased de novo synthesis during adaptation over 24 hours Cellular capacity to degrade oxidatively damaged proteins increased with 20S proteasome, immunoproteasome, and PA28αβ synthesis, and was mostly blocked by 20S proteasome, immunoproteasome, and PA28 siRNA knock-down treatments. Additionally, PA28αβ knockout mutants achieved only half the H(2)O(2) induced adaptive increase in proteolytic capacity of wild-type controls. Direct comparison of purified 20S proteasome and immunoproteasome demonstrated that immunoproteasome can selectively degrade oxidized proteins. Cell proliferation and DNA replication both decreased, and oxidized proteins accumulated, during high H(2)O(2) challenge, but prior H(2)O(2) adaptation was protective. Importantly, siRNA knock-down of 20S proteasome, immunoproteasome, or PA28αβ regulator blocked 50–100% of these adaptive increases in cell division and DNA replication, and immunoproteasome knock-down largely abolished protection against protein oxidation.